Facilitating India-Pakistan trade through the land route - Nisha Taneja; Isha Dayal; Samridhi Bimal (Indian Council for Research on International Economic Relations (ICRIER), 2016)
Improvements in the land route between India and Pakistan can help lower transaction costs which can play in important role in realizing the trade potential between the two countries. Connecting India and Pakistan by the land route offers gains not only to the two countries but would spread over a wide geography covering several countries. With the vision of connecting India and Pakistan to Central Asia and East Asia, this paper makes an attempt to examine trade between India and Pakistan by different modes of transport, identify physical and non-physical impediments to transporting goods by rail and road while taking into account the implications of trade policy for transporting goods; suggests measures to address these constraints which are also in compliance with the provisions in the recently signed WTO Agreement on Trade Facilitation. The paper also suggests how acceding to international conventions will make it easier for the two countries to connect with the rest of the world.
Keywords: F10; F13; R40; F53; 330; India-Pakistan; Trade; Trade Facilitation; WTO Trade Facilitation Agreement